Etos aktywności ekonomicznej w świetle encykliki Caritas in Veritate Benedykta XVI - Kowalczyk, ks. Stanisław (Annales. Etyka w Życiu Gospodarczym, 2012)
Liberalism and marxism are two forms of economism, which separate economic activity from ethics. The social teaching of the Church accepted continued by pope Benedict XVI recognizes the necessity of free market and limited intervention of the state in economy, but first of all postulates creativity of civil society in the field of economic life. The main arguments for observance of moral rules in the economic activity are following: 1. Every conscious and free men’s action is responsible for the effects – economic activity cannot be any exception; 2. The same ethics ought to be applied in the individual-private life and in the public domain – also economy; 3. Ethos of economic activity is connected with three virtues – truth, love and justice (also social justice); 4. Christian-personalistic ethics is based on the principles auxialiarity (personalism) and common good (solidarity). Economic activity completely separated from ethics is inhuman.